2020
DOI: 10.1111/1753-0407.13028
|View full text |Cite
|
Sign up to set email alerts
|

Detection of diabetes and prediabetes using glycosylated hemoglobin in Chinese adults living in Shanghai: A prospective analysis

Abstract: BackgroundThis study aimed to evaluate the discriminative abilities of glycosylated hemoglobin (HbA1c) and to examine the optimal HbA1c cutoff values for diabetes and prediabetes in Chinese adults.MethodsData of a population‐based cohort of Chinese adults aged ≥40 years living in Jiading District in Shanghai were used. At baseline, 9389 and 7241 participants were included to identify the optimal HbA1c cutoff values for diabetes and prediabetes, respectively using the 1999 World Health Organization criteria as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“… 54 However, Wang et al reported that around 64.6% of the individuals had an educational level at higher school or above in Shanghai. 47 For occupational status, Belfki et al indicated more than half (56.6%) of the participants were retired or had no current jobs. 54 The corresponding proportion was only 24.2% in Cuong et al ’s study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 54 However, Wang et al reported that around 64.6% of the individuals had an educational level at higher school or above in Shanghai. 47 For occupational status, Belfki et al indicated more than half (56.6%) of the participants were retired or had no current jobs. 54 The corresponding proportion was only 24.2% in Cuong et al ’s study.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies stated the participants’ alcohol consumption; one reported a higher rate (79.8%), 45 compared with that reported in two studies (10.5%–13.64%). 47 52 Among the five studies which included physical activity, three of them reported that more than half of the participants performed adequate physical activity (60.5%–71.2%) 29 47 58 ( table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Questions for formative assessments, demographic background, health status, dietary habits and participant's lifestyle preferences were extracted from Michigan Diabetes care profile tests 19 . Study subjects were escorted to the diagnostic laboratory for their hemoglobin A1c (HbA1C), and a fasting serum insulin test was performed according to a standard protocol with cut-off values specified by the World Health Organization (WHO) 20 . BMI was recorded for each participant.…”
Section: Methodsmentioning
confidence: 99%